2019
DOI: 10.1002/hbm.24830
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐band oscillations play an essential role in motor–auditory interactions

Abstract: In the human brain, self-generated auditory stimuli elicit smaller cortical responses compared to externally generated sounds. This sensory attenuation is thought to result from predictions about the sensory consequences of self-generated actions that rely on motor commands. Previous research has implicated brain oscillations in this process. However, the specific role of these oscillations in motor-auditory interactions during sensory attenuation is still unclear. In this study, we aimed at addressing this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 60 publications
5
41
0
Order By: Relevance
“…As seen in the current and many previous studies, phase reset and entertainment of ongoing oscillations is most prevalent in extragranular layers (Lakatos et al, 2005a(Lakatos et al, , 2007(Lakatos et al, , 2009O'Connell et al, 2011), and modulatory inputs targeting these layers have long thought to cause phase reset, and if stimuli are rhythmic, entrainment (Barczak et al, 2019;Lakatos et al, 2009;O'Connell et al, 2011O'Connell et al, , 2014. Besides anatomical studies, recent magnetoencephalography studies investigating predictions in auditory scenes in humans found significant effective connectivity from motor cortex toward auditory areas (Abbasi and Gross, 2020;Morillon and Baillet, 2017). Additionally, besides direct projections, an indirect source of motor influences on the auditory system could stem from the cochlea, as a recent study reported oscillations of the eardrum coinciding with saccade onset in the absence of sound (Gruters et al, 2018).…”
Section: The Circuitry Of Saccade Related Entrainment In A1supporting
confidence: 50%
“…As seen in the current and many previous studies, phase reset and entertainment of ongoing oscillations is most prevalent in extragranular layers (Lakatos et al, 2005a(Lakatos et al, , 2007(Lakatos et al, , 2009O'Connell et al, 2011), and modulatory inputs targeting these layers have long thought to cause phase reset, and if stimuli are rhythmic, entrainment (Barczak et al, 2019;Lakatos et al, 2009;O'Connell et al, 2011O'Connell et al, , 2014. Besides anatomical studies, recent magnetoencephalography studies investigating predictions in auditory scenes in humans found significant effective connectivity from motor cortex toward auditory areas (Abbasi and Gross, 2020;Morillon and Baillet, 2017). Additionally, besides direct projections, an indirect source of motor influences on the auditory system could stem from the cochlea, as a recent study reported oscillations of the eardrum coinciding with saccade onset in the absence of sound (Gruters et al, 2018).…”
Section: The Circuitry Of Saccade Related Entrainment In A1supporting
confidence: 50%
“…Interareal synchronization of alpha (α, 7-14 Hz) and beta (β, 14-30 Hz) oscillations in humans and nonhuman primates, respectively, is thought to regulate top-down or feedback communication [14][15][16][17][18][19]. In contrast, both β and gamma-band (γ, 30-100 Hz) oscillations and synchronization have been associated with bottom-up sensory processing and representation of object-specific sensory information [15,[20][21][22], and β oscillations are also associated with sensorimotor processing [23,24]. Overall, brain-wide oscillation networks in multiple frequencies are proposed to be the core of cognition [10,11,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, large-scale oscillatory networks in several frequency bands characterize magnetoencephalography (MEG), electroencephalography (EEG), and stereo-EEG (SEEG) data during resting state (RS) activity [3][4][5][6][7][8] and in many cognitive functions [9][10][11][12][13]. Inter-areal synchronization of alpha (, 7-14 Hz) and beta (, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz) oscillations in humans and non-human primates, respectively, is thought to regulate top-down or feedback communication [14][15][16][17][18][19]. In contrast, both  and gamma-band (, 30-100 Hz) oscillations and synchronization have been associated with bottom-up sensory processing and representation of object-specific sensory information [15,[20][21][22], and  oscillations are also with sensorimotor processing [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Inter-areal synchronization of alpha (, 7-14 Hz) and beta (, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz) oscillations in humans and non-human primates, respectively, is thought to regulate top-down or feedback communication [14][15][16][17][18][19]. In contrast, both  and gamma-band (, 30-100 Hz) oscillations and synchronization have been associated with bottom-up sensory processing and representation of object-specific sensory information [15,[20][21][22], and  oscillations are also with sensorimotor processing [23,24]. Overall, brain-wide oscillation networks in multiple frequencies are proposed to be the core of cognition [10,11,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%